ANALISIS PERHITUNGAN UNIT COST PELAYANAN SIRKUMSISI DENGAN PENDEKATAN ABC DI KLINIK SETIA BUDI JAMBI - Didik Afrida; Firman Pribadi; Triyani Marwati (Universitas Muhammadiyah Yogyakarta, 2013)
Circumcision costing couter and conventional methods in Setia Budi Clinic Jambi using traditional accounting systems, so the services offered to be cheaper (under costing) or more expensive (over costing) of the costs that should be consumed on these services. It would be fatal to the hospital, especially in a highly competitive market conditions. Thus researchers need to review the unit cost in the circumcision services costing more accurate in the details of the cost and accuracy of charging better, then a decision will be taken by the management would be better and appropriate. Research performed using a qualitative descriptive design. Instruments used were documentation guidelines owned by hospital and stopwatch. Cost analysis method used is based on ABC (Activity Based Costing) system. The results of this study show units of cost to perform circumcision services at Setia Budi Clinic Jambi which is calculated using the Activity Based Costing (ABC) system is Rp 240.242,59 for the M conventional services and Rp 385.200,57 for M couter services. From the calculation of unit cost pelayananan circumcision in Clinical Setia Budi Jambi is calculated using the ABC method gives results smaller M convenstional service. While in service M couter, ABC calculation gives greater results.